Exposure-response relations for work related respiratory symptoms and sensitisation in a cohort exposed to alpha-amylase. - Brisman, J; Nieuwenhuijsen, M; Venables, K; Putcha, V; Gordon, S; Taylor, A (2004)
AIMS: To explore relations between exposure to fungal alpha-amylase and the risk of new work related respiratory symptoms or sensitisation. METHODS: A prospective cohort study among 300 bakers and millers was followed up for a maximum of seven years. Exposure to alpha-amylase was estimated by air measurements and questionnaires and classified into three categories. Symptoms were recorded with a self-administered questionnaire and skin sensitisation assessed using skin prick test (SPT). RESULTS: There were 36 new cases of chest symptoms, 86 of eyes/nose symptoms, and 24 of a positive SPT to alpha-amylase. There were exposure-response relations for chest and eyes/nose symptoms and for sensitisation, and a significantly increased prevalence ratio for chest symptoms in the highest exposure category. CONCLUSION: A reduction in alpha-amylase exposure is likely to reduce the risk for respiratory morbidity in bakery workers.